Effects of prolonged unemployment and reemployment on psychological and physical health - Galić, Zvonimir (Array, 2008)
The purpose of the present study was to explore the impact of prolonged unemployment and reemployment on a both psychological and physical health over a period of more than two years. In a three-way longitudinal survey of initially unemployed persons in Croatia, we examined the self-assessed physical and mental health, captured by the SF-36 Health Survey, as a group of unemployed persons moved into employment or remained unemployed. The results confirmed that only psychological health depends on the participant’ s employment status, while physical health wasn’ t related to prolonged unemployment or (re)employment.